Evaluasi Penyakit ISPA pada Masyarakat Kelurahan Taratara Satu Kecamatan Tomohon Barat Kota Tomohon - Maddusa, Sri Seprianto; Asrifuddin, Afnal; Rumengan, Adeleide; Sabandar, Fridela; Lantho, Graselin; Sinaga, Patricia; Polii, Okan; Mumek, Vanessa; Mamahit, Viola; Yosabam, Reagen (Pakis Journal Institute, 2025)
The Field Learning Practice (PBL) III in Taratara Satu Village was carried out to evaluate the effectiveness of previous interventions related to Acute Respiratory Infections (ARI/ISPA). The intervention involved installing educational billboards at the village office and a local motorcycle taxi station. Evaluation methods included observation, interviews, and online questionnaires. The results showed that the billboard at the village office remained intact and effective as an educational tool, while the one at the motorcycle station was damaged due to weather. Residents reported a better understanding of ISPA prevention after the intervention. Overall, the program was considered successful in raising community awareness, although environmental factors still posed challenges. The results of the activity showed that this intervention was effective in increasing public understanding of the prevention of ISPA and encouraging changes in healthy living behaviors. This emphasizes the importance of sustainability and maintenance of physical educational media to ensure that health messages can be conveyed optimally.